2009
DOI: 10.1177/0894845308327270
|View full text |Cite
|
Sign up to set email alerts
|

From Drafter to Engineer, Doctor to Nurse

Abstract: This article explored career compromise as negotiated by working-class adults pursuing science-related careers. Using a multiple case study method, we focused on eight individuals who participated in an interview about their career choices and then were followed longitudinally for 2 years. All participants were first-generation college students from working-class families and, at the start of the study, were enrolled at a community college. The results highlight key factors that influenced initial compromises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Third, it should be emphasized that causality cannot be inferred from the relationships in the final structural model, as the conditions for establishing causality (e.g., Hair et al, 2006) were not met. Fourth, it is acknowledged that not all the variables or constructs that may be related to the vocational decision-making processes of adolescents were investigated and that an implicit assumption has been made that career choice may be independent of other decisions and the individual contexts of the decision maker (Cherkaoui, 2003;Packard & Babineau, 2009;Patton & McMahon, 2006;Veselý & Smith, 2008). Finally, it is noted that a ''good'' fit of the empirical model does not necessarily guarantee that it is the ''optimal'' model for the data (Hair et al, 2006).…”
Section: Limitations Of the Researchmentioning
confidence: 99%
“…Third, it should be emphasized that causality cannot be inferred from the relationships in the final structural model, as the conditions for establishing causality (e.g., Hair et al, 2006) were not met. Fourth, it is acknowledged that not all the variables or constructs that may be related to the vocational decision-making processes of adolescents were investigated and that an implicit assumption has been made that career choice may be independent of other decisions and the individual contexts of the decision maker (Cherkaoui, 2003;Packard & Babineau, 2009;Patton & McMahon, 2006;Veselý & Smith, 2008). Finally, it is noted that a ''good'' fit of the empirical model does not necessarily guarantee that it is the ''optimal'' model for the data (Hair et al, 2006).…”
Section: Limitations Of the Researchmentioning
confidence: 99%
“…However, considering the uncertain and ever-changing career climate, young people may need to take any job that is available (Briscoe, Hall, & DeMuth, 2006). It is then questionable whether a person will be able to maintain direction and a sense of purpose while settling down to a particular job, or whether such a choice is tinged with regret or loss (Packard & Babineau, 2009). Given these social and economic changes, a more comprehensive understanding of career adaptability is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, employees may also accept horizontal mismatch in exchange for job security provided by permanent contracts 33 . Packard et al (2009) suggested that heavy family responsibilities could lead to career compromise 34 . As a result, high-level medical talents may also compromise to accept careers that do not exactly match their college major to accumulate social resources and gain income for reasons of needing to take care of their families.…”
Section: Major Matchmentioning
confidence: 99%